Analisa Beban Kerja Dengan Metode Full Time Equivalent DAN NASA-TLX Untuk Menentukan Jumlah Tenaga Kerja Optimal Pada Unit Assy-Disassy (TVP-1) Engine Services PT. GMF Aeroasia Tbk - Raharjo, Yoyok Muji; Ariyanti, Silvi (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
PT. GMF AeroAsia is a company engaged in aircraft maintenance or MRO (Maintenance, Repair, and Overhaul). The problem in this research is the high overtime in the Assist-Disassy Unit (TVP-1) caused in completing the treatment process as much as possible in accordance with the predetermined Turn Around Time (TAT). The research method used is Full Time Equivalent (FTE) and NASA-TLX which aims to measure physical and mental workload, calculate the optimal number of employees and determine proposed improvements to improve these conditions. Based on the results of the FTE analysis, the physical workload received from a total of 15 were 6 people in the overload category consisting of 2 Engineers and 4 Senior Technicians. Meanwhile, from the results of the NASA-TLX analysis, the mental workload accepted by the Engineer position with an average score of 79.92 is categorized as High mental workload. While in the position of Senior Technician with an average score of 83.86, the mental workload category is Very High. The optimal number of Assy-Disassy Unit (TVP-1) manpower.